EFFECT OF INFORMATION TECHNOLOGY INFRASTRUCTURE ON CUSTOMER RELATIONSHIP MANAGEMENT IN PRIVATE HOSPITALS IN KENYA - Muthigah, Faithmercy; Kiragu, David; Sang , Anne (European Journal of Business and Strategic Management, 2021)
Purpose: The purpose of this study was to establish the effect of information technology infrastructure on customer relationship management in private hospitals in Kenya Materials and Methods: The study adopted descriptive survey design. It targeted 161 private hospitals which are accredited by NHIF in Kenya and which formed the unit of analysis of the study. Simple random sampling was then be used to obtain the 644 respondents. The researcher utilized a structured questionnaire with a five-point Likert scale to gather the data. The collected data was coded and entered in SPSS for further analysis. Descriptive and inferential analysis was conducted. Before inferential analysis was conducted, diagnostics tests were done. Results: The findings indicate there was a statistical and significant relationship between information technology infrastructure and customer relationship management. Therefore, the research theory was rejected and the substitute hypothesis that information technology infrastructure has a statistically significant effect on CRM in private hospital was supported. The results show that if private hospitals enhanced their technology initiatives such as interconnecting operating systems, installing human-friendly machine system and improving network and telecommunication technology, patients would be satisfied with their services and would come back or refer a friend. Unique contribution to theory, practice and policy: The study recommends that hospitals ought to enhance their CRM policies so as to deliver quality services that satisfy Information technology infrastructure can revolutionize healthcare with the right policy choices. IT can foster new human connectivity thresholds and is a powerful tool of global convergence through the cross-border provision of services and can as well provide new opportunities for the production of knowledge and skills.